Surface and dual-Doppler radar analysis of 23-24 June 1985 OK PRE-STORM heat bursts - Bernstein, Ben Carter, author (Colorado State University. Libraries, 1990)
Doppler radar data are used to investigate heat bursts which accompanied a mesoscale convective system that traversed the OK PRE-STORM mesonetwork on 23-24 June 1985. The three dimensional structure of the precipitation and wind fields are discussed in an effort to uncover the cause of strong downdrafts which lead to the formation of heat bursts. Surface mesonetwork data are presented to depict the changes in temperature, dew point, relative humidity, Be, wind speed and wind direction which characterize them. Digitized WSR-57 radar data are used to detail the progression of the MCS, and a sounding is used to give an indication of the vertical structure of the temperature, dew point and wind fields in the vicinity of the heat bursts. The 23-24 June MCS formed along a dry line in western Kansas. As the system matured, an area of stratiform precipitation developed behind a line of convective towers which moved southeast with time. Southwesterly flow at upper levels caused the stratiform precipitation to extend northeastward, allowing it to become isolated from the convective line. A broad surface mesohigh was observed beneath the core of the stratiform region. This feature \Vas flanked by sharp pressure gradients and mesolows to its northwest, north and northeast. It was within these mesolows that the heat bursts occurred. Time series of surface mesonetwork data show that heat bursts are characterized by sudden dramatic rises in temperature and falls in dew point. Strong, gusty winds and modest falls in Be also accompanied the bursts. These changes are attributed to the removal of a shallow, moist stable layer at the surface by an intrusion of warm , dry air from aloft. A 600 km2 area of winds greater than 15 m s-1 was detected near the surface by the CP-3 Doppler radar. This wind maximum developed in an area of low reflectivity on the northeastern edge of the stratiform extension. These features moved southeast with time, and passed over one station in the mesonetwork, PAM-12. Their passage corresponded in time with the occurrence of heat bursts at that station. Dual-Doppler syntheses for 5-10 minutes preceding the onset of the heat bursts reveal an anvil-like structure in the precipitation field over PAM-12. Stratiform precipitation was falling just to the west of the station, and a strong reflectivity gradient existed at the edge of this precipitation . A strong mesoscale inflow entered the anvil cloud region at mid-levels, descended along the base of the anvil and reached the surface in the area of the strong reflectivity gradient. Downdrafts reaching 3 m s-1 were observed there. The winds detected in this region are used· to infer winds which may have existed in the precipitation free portion of the stratiform anvil. It is proposed that this lateral inflow jet warmed dry adiabatically as it descended, deformed the surface stable layer and caused a dramatic warming and drying at PAM-12.
November 1990.
Also issued as author's thesis (M.S.) -- Colorado State University, 1990.
Keywords: Convection (Meteorology); Doppler radar